PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE JIGSAW UNTUK MENGATASI KESALAHAN SISWA MENYELESAIKAN SOAL PADA POKOK BAHASAN FAKTORISASI SUKUALJABAR KELAS VIII SEMESTER GANJILSMP NEGERI 11 JEMBER TAHUN AJARAN 2013/2014 - Ati’ah, Siti; Pambudi, Didik Sugeng; Trapsilasiwi, Dinawati (Department of Mathematics Education , University of Jember, 2014)
Abstract.There are manystudentswhohave difficultyin solvingmath problems. Difficultiesresulted instudentsmaking mistakein solvingproblems.The kinds of student’s mistakes consist of the use of data errors, error of theorem or definition, technical errors, language interpretation errorsand another errors. Therefore, appliedcooperative learning modelof jigsaw type toovercome thestudent’smistakes in solvingthe Algebraic Factorization problems at eighthgradeSMP Negeri 11 Jemberacademic year2013/2014. This research design is Classroom Action Research (CAR). Basedon this research,the application ofcooperative learning modelof jigsaw type canincrease the activity ofstudentsanddecreasestudent’s mistakesin solvingAlgebraic Factorization.The percentage ofeffectivenesson the first cycle of 43.23 % and 33.05 % for the second cycle . So it can be concluded that the application of cooperative learning model of jigsaw type is effective enough to overcome student’s mistakesin solving Algebraic Factorization. Key Words: Cooperative learning model of jigsaw type, algebraic factorization, student’s activity, student’s mistakes